Spinal Arteriovenous Fistulas of the Filum Terminale - Lim, S.M.; Choi, I.S.; David, C.A. (American Journal of Neuroradiology, 2011)
SUMMARY: The filum terminale is an anatomic structure at the end of the spinal cord. Only a few cases of AVFs of the filum terminale have been reported. These AVFs usually consist of a single communication between the anterior spinal artery and a single draining vein. We retrospectively analyzed the clinical and radiologic features and treatment of 4 patients with spinal AVFs of the filum terminale. Clinical manifestations and MR images are similar to those of spinal dural AVFs. All patients underwent surgical or endovascular treatment, resulting in complete occlusion. Clinical outcomes were good to excellent in all patients. ASAanterior spinal arteryAVFarteriovenous fistulaAVMarteriovenous malformationAVSarteriovenous shuntEndovasendovascular embolizationn-BCAn-butyl cyanoacrylateSIsignal intensitySVsignal voids